Electronic structure, phase stability, and vibrational properties of Ir-based intermetallic compound IrX (X=Al, Sc, and Ga). (February 2015) - Arıkan, N.; Charifi, Z.; Baaziz, H.; Uğur, Ş.; Ünver, H.; Uğur, G.
Abstract: The phase stability and mechanical properties of B2 type IrX (X=Al, Sc and Ga) compounds are investigated. Self-consistenttotal-energy calculations in the framework of density functional theory using the Generalized Gradient Approximation (GGA) to determine the equations of state and the elastic constants of IrX (X=Al, Sc, and Ga) in the B2 phase have been performed. The calculations predicted the equilibrium lattice constants, which are about 1% greater than experiments for IrAl, 1.81% for IrGa, and 0.71% for IrSc compound. IrAl is shown to be the least compressible, and it is followed by IrGa and the IrSc compound. The phase stability of the studied compounds is checked. The brittleness and ductility properties of IrX (X=Al, Sc, and Ga) are determined by Poisson's ratio σ criterion and Pugh's criterion. IrGa compound is a ductile material; however, IrAl and IrSc show brittleness. The band structure and density of states (DOS), and phonon dispersion curves have been obtained and analyzed. The position of the Fermi level and the contribution of d electrons to the density of states near E F is studied and discussed in detail. We also used the phonon density of states and quasiharmonic approximation to calculate and predict some thermodynamic properties such as constant-volume specific heat capacity of the B2 phase of IrX (X=Al, Sc and Ga) compounds. Graphical abstract: Highlights: We present electronic and phonon band structure of IrX (X= Al, Sc and Ga). Elastically, all the compounds have been found to be stable. IrX (X= Al, Sc and Ga) exhibit metallic characters.